Broad protection against clade 1 sarbecoviruses after a single immunization with cocktail spike-protein-nanoparticle vaccine - Halfmann, Peter J.; Loeffler, Kathryn; Duffy, Augustine; Kuroda, Makoto; Yang, Jie E.; Wright, Elizabeth R.; Kawaoka, Yoshihiro; Kane, Ravi S. (Nature communications, 2024)
The 2002 SARS outbreak, the 2019 emergence of COVID-19, and the continuing evolution of immune-evading SARS-CoV-2 variants together highlight the need for a broadly protective vaccine against ACE2-utilizing sarbecoviruses. While updated variant-matched formulations are a step in the right direction, protection needs to extend beyond SARS-CoV-2 and its variants to include SARS-like viruses. Here, we introduce bivalent and trivalent vaccine formulations using our spike protein nanoparticle platform that completely protect female hamsters against BA.5 and XBB.1 challenges with no detectable virus in the lungs. The trivalent cocktails elicit highly neutralizing responses against all tested Omicron variants and the bat sarbecoviruses SHC014 and WIV1. Finally, our 614D/SHC014/XBB trivalent spike formulation completely protects human ACE2-transgenic female hamsters against challenges with WIV1 and SHC014 with no detectable virus in the lungs. Collectively, these results illustrate that our trivalent protein-nanoparticle cocktail can provide broad protection against SARS-CoV-2-like and SARS-CoV-1-like sarbecoviruses. Evolution of SARS-CoV-2 and emergence of other sarbecoviruses are of potential concern. Here, the authors designed a trivalent spike-protein-nanoparticle vaccine that elicits neutralizing antibodies and protects female hamsters against challenges with SARS-CoV-2-like and SARS-CoV-1-like coronaviruses.